Immune Regulatory Properties of Allogeneic Adipose-Derived Mesenchymal Stem Cells in the Treatment of Experimental Autoimmune Diabetes - Bassi, Ênio J. (American Diabetes Association, 2012)
Adipose-derived mesenchymal stem cells (ADMSCs) display immunosuppressive properties, suggesting a promising therapeutic application in several autoimmune diseases, but their role in type 1 diabetes (T1D) remains largely unexplored. The aim of this study was to investigate the immune regulatory properties of allogeneic ADMSC therapy in T cell–mediated autoimmune diabetes in NOD mice. ADMSC treatment reversed the hyperglycemia of early-onset diabetes in 78% of diabetic NOD mice, and this effect was associated with higher serum insulin, amylin, and glucagon-like peptide 1 levels compared with untreated controls. This improved outcome was associated with downregulation of the CD4(+) Th1-biased immune response and expansion of regulatory T cells (Tregs) in the pancreatic lymph nodes. Within the pancreas, inflammatory cell infiltration and interferon-γ levels were reduced, while insulin, pancreatic duodenal homeobox-1, and active transforming growth factor-β1 expression were increased. In vitro, ADMSCs induced the expansion/proliferation of Tregs in a cell contact–dependent manner mediated by programmed death ligand 1. In summary, ADMSC therapy efficiently ameliorates autoimmune diabetes pathogenesis in diabetic NOD mice by attenuating the Th1 immune response concomitant with the expansion/proliferation of Tregs, thereby contributing to the maintenance of functional β-cells. Thus, this study may provide a new perspective for the development of ADMSC-based cellular therapies for T1D.